Diagnostic value of cutaneous manifestation of SARS‐CoV‐2 infection*. (1st May 2021) - Visconti, A.; Bataille, V.; Rossi, N.; Kluk, J.; Murphy, R.; Puig, S.; Nambi, R.; Bowyer, R. C. E.; Murray, B.; Bournot, A.; Wolf, J.; Ourselin, S.; et al.
Summary: Background: One of the challenging aspects of SARS‐CoV‐2 infection is its diverse multisystemic disease presentation. Objectives: To evaluate the diagnostic value of cutaneous manifestations of SARS‐CoV‐2 infection and investigate their duration and timing in relation to other COVID‐19 symptoms. Methods: We used data from 336 847 UK users of the COVID Symptom Study app to assess the diagnostic value of body rash or an acral rash in SARS‐CoV‐2 infection, and data from an independent online survey of 11 544 respondents to investigate skin‐specific symptoms and collect their photographs. Results: Using data from the app, we show significant association between skin rashes and a positive swab test result (odds ratio 1·67, 95% confidence interval 1·42–1·97). Strikingly, among the respondents of the independent online survey, we found that 17% of SARS‐CoV‐2‐positive cases reported skin rashes as the first presentation, and 21% as the only clinical sign of COVID‐19. Together with the British Association of Dermatologists, we have compiled a catalogue of images of the most common skin manifestations of COVID‐19 from 400 individuals (https://covidskinsigns.com ), which we have made publicly available to assist clinicians in recognition of this early clinical feature of COVID‐19. Conclusions: Skin rashes cluster with other COVID‐19 symptoms, are predictive of a positive swab test, and occur in a significant number of cases, either alone or before other classical symptoms. Recognizing rashes is important in identifying new and earlier cases of COVID‐19.